Retroperitoneal Castlemans disease mimicking a liver cancer: a case report - Kang, Mao-Ji; Zhang, Jin-Chang; Fang, Cheng; Li, Bo; Su, Song (Frontiers in Oncology, 2024)
Castleman disease (CD), a distinct lymphoproliferative disorder, is infrequently encountered in clinical practice and poses significant diagnostic challenges. We present the case of a 48-year-old asymptomatic female, admitted for evaluation of a hepatic mass detected in the liver's right lobe. Preoperative laboratory tests were within normal limits. Diagnostic imaging, including contrast-enhanced magnetic resonance imaging (MRI), was suggestive of hepatocellular carcinoma. Furthermore, contrast-enhanced abdominal computed tomography (CT) scans were indicative of hepatic malignancy. Subsequently, the patient underwent laparoscopic surgery targeting a retroperitoneal mass. During the surgical procedure, it was observed that the tumor was a retroperitoneal mass situated posterior to the liver, exhibiting localized adhesion to hepatic tissue. The postoperative histopathological analysis revealed the mass to be hyaline-vascular type Castleman disease (HV-CD), thereby refuting the initial diagnosis of a hepatic malignancy. This case underscores the complexity of diagnosing retroperitoneal Castleman disease, particularly when it masquerades as a hepatic tumor.